Ecology and strategy - Baum, Joel A. C.; Dobrev, Stanislav D.; Witteloostuijn, Arjen van (Emerald, 2006)
Volume 23 of the Advances in Strategic Management series focuses on ecology and strategy, providing an excellent point of reference for scholars, students and practitioners of business. The nine-part volume addresses diverse fields such as the U.S. motion picture, British motorcycle, and optical disk drive industries. The authors included represent institutions of higher learning from around the world, giving this latest edition international appeal. There is international representation. It addresses the human ecology of organizations, the relationship between the employee and the company. It includes papers regarding the US Motion Picture, British Motorcycle, and Optical Disk Drive industries.
Keywords: Organizational change.; Organizational behavior.; elektronické knihy; electronic books